Ahmadiyya in Islam: teachings and developments (Texas Journal of Multidisciplinary Studies, 2022)
Ahmadiyah has a different view regarding the concept of "khataman nabiyin" for most Muslims it means the end of prophethood after the Prophet Muhammad. However, for Ahmadiyah it does not mean the end of prophethood, but the prophet sent is a prophet who still adheres to the teachings of the Prophet Muhammad. A prophet without sharia is the point of view of the Ahmadiyya